Interlayer Structure of Bioactive Molecule, 2-Aminoethanesulfonate, Intercalated into Calcium-Containing Layered Double Hydroxides. (6th June 2012) - Kim, Tae-Hyun; Kim, Hyoung Jun; Oh, Jae-Min
Abstract : We have successfully intercalated 2-aminoethanesulfonate, a well-known biomolecule taurine, into calcium-containing layered double hydroxides via optimized solid phase intercalation. According to X-ray diffraction patterns and infrared spectroscopy, it was revealed that the intercalated taurine molecules were each directly coordinated to other calcium cation and arranged in a zig-zag pattern. Scanning electron microscopy showed that the particle size and morphology of the LDHs were not affected by the solid phase intercalation, and the surface of intercalates was covered by organic moieties. From ninhydrin amine detection tests, we confirmed that most of the taurine molecules were well stabilized between the calcium-containing LDH layers.